Multicenter experience with valve‐in‐valve transcatheter aortic valve replacement compared with primary, native valve transcatheter aortic valve replacement. Issue 12 (30th November 2022) - Robich, Michael P.; Iribarne, Alexander; Butzel, David; DiScipio, Anthony W.; Dauerman, Harold L.; Leavitt, Bruce J.; DeSimone, Joseph P.; Coylewright, Megan; Flynn, James M.; Westbrook, Benjamin M.; Ver Lee, Peter N.; Zaky, Mina; et al.
Abstract: Background: Valve‐in‐valve (ViV) transcatheter aortic valve replacement (TAVR) offers an alternative to reoperative surgical aortic valve replacement. The short‐ and intermediate‐term outcomes after ViV TAVR in the real world are not entirely clear. Patients and Methods: A multicenter, retrospective analysis of a consecutive series of 121 ViV TAVR patients and 2200 patients undergoing primary native valve TAVR from 2012 to 2017 at six medical centers. The main outcome measures were in‐hospital mortality, 30‐day mortality, stroke, myocardial infarction, acute kidney injury, and pacemaker implantation. Results: ViV patients were more likely male, younger, prior coronary artery bypass graft, "hostile chest, " and urgent. 30% of the patients had Society of Thoracic Surgeons risk score <4%, 36.3% were 4%–8% and 33.8% were >8%. In both groups many patients had concomitant coronary artery disease. Median time to prosthetic failure was 9.6 years (interquartile range: 5.5–13.5 years). 82% of failed surgical valves were size 21, 23, or 25 mm. Access was 91% femoral. After ViV, 87% had none or trivial aortic regurgitation. Mean gradients were <20 mmHg in 54.6%, 20–29 mmHg in 30.6%, 30–39 mmHg in 8.3% and ≥40 mmHg in 5.87%. Median length of stay was 4 days. In‐hospital mortality was 0%. 30‐day mortality was 0% in ViV and 3.7% in native TAVR. There was no difference in in‐hospital mortality, postprocedure myocardial infarction, stroke, or acute kidney injury. Conclusion: Compared to native TAVR, ViV TAVR has similar peri‐procedural morbidity with relatively high postprocedure mean gradients. A multidisciplinary approach will help ensure patients receive the ideal therapy in the setting of structural bioprosthetic valve degeneration.